Presença da educação brasileira na base de dados Francis® : uma abordagem bibliométrica - Hayashi, Carlos Roberto Massao (2004)
This work had as objective a bibliometric analysis of the brazilian scientific production on the education thematic, present in an international database, a database Francis® of the Institut de l`Information Scientifique et Technologique INIST of the Centre National de la Recherche Scientifique - CNRS, in the France. The adopted methodology was developed in two stages: first, revision of literature of the research and scientific production in education, scientific communication, databases and bibliometrics studies. The second, constituted of the information collected in the database FrancisÒ: autors, authors affiliation, publication type, keywords, publication language, editor country, publication year, imprenta, abstracts, terms french, english, spanish, among others. The gotten results had been analyzed using automatized tools for treatment and bibliometric analysis. We can appoint that the scientific production in the education area in the Brazil have an important presence in the database Francis® and information visibility and accessibility on education in Brazil.